Modelling and forecasting of primary timber-based industry In Peninsular Malaysia - Abdul Wahob, Noraida (2014)
Malaysia is one of the major producing countries in global timber market. The Malaysian Government has put priority to the implementation of Sustainable Forest Management (SFM) practices. Recognizing the need to strengthen the SFM practices, Malaysia has undertaken a critical step to reduce the Annual Allowable Cutting (AAC) and has imposed stringent criteria on timber harvesting operations. As a result, this policy implementation has influenced the volume of timber that can be extracted from the natural forests which has and simultaneously affected the timber processing industry in Peninsular Malaysia. Hence, impact analysis of SFM practices on timber-based industries in Peninsular Malaysia is needed. This study covered timber-based products namely s sawn timber, veneer and plywood and those representing the first stage of timber-based processing industry. The data used are were annual time series from 1980 until 2012 which are obtained from three major resources namely; the Statistics Forestry Department Peninsular Malaysia, the Malaysian Timber Industry Board Resource Center and the World Bank. The analysis of each commodity uses 4 models; specifically, the supply model, domestic demand model, import demand model and export demand model. The Augmented Distribution Lagged (ARDL) is employed in order to get the goodness of fit for each commodity model. This model provides short run and long run coefficients which are being used for impact analysis. Based on the supply model of the sawn timber, the results show that harvested area is statistically significant at 5% level in determining the production of sawn timber. The domestic price of plywood is highly significant at 1% level in determining plywood supply. Whereas in domestic demand model, import prices of veneer and sawn timber are statistically significant at 5% and 10% level respectively. For export demand model, the export price of sawn timber and veneer are highly significant at 1% level. Lastly, for the import demand model, the import price for sawn timber and veneer shows that they are statistically significant at 5% and 10% level respectively. Moving on to the forecasting analysis, each timber commodity has been forecasted based on four scenarios under SFM practices, namely; (1) reduction by 20% in harvested area, (2) a rise by 25% in price of commodity; (3) rise by 47% in input cost; (4) integration of scenario 1, 2 and 3 and; (5) rise by 10% in the Contribution of Forestry Activity and Harvesting to Total Gross Domestic Products (CGDP). The results revealed that, the most affected SFM practices are on veneer and plywood. In the production of veneer and plywood, particularly when the scenario is imposed, production tended to decrease. Henceforth, the results suggest that, producers tend to decrease production of veneer and plywood due to SFM practices since both commodities are produces in came from the same mill. On the other hand, consumers of veneer and plywood products for the making of value-added product such as furniture has to import the commodity, since the availability of veneer and plywood are scares. However, the trend in the production of sawn timber has been constantly increasing even after the imposition of the scenario under SFM practices. This indicates that, the production of sawn timber has been continuously, growing with SFM practices. The result suggested that, the producers would be able to produce more sawn timber after imposing the scenario under SFM practices. Thus, such SFM practices certainly help generate economic growth in the timber-based sector besides its sustainability. It will also help to enhance forest conservation goal in Peninsular Malaysia.